Peningkatan Literasi Teknologi Jaringan Komputer dan Keterampilan Berbicara Siswa di SMA Moria Kota Sorong (Kesejahteraan Bersama : Jurnal Pengabdian dan Keberlanjutan Masyarakat, 2026)
The development of information and communication technology requires students to have digital literacy and communication skills as essential competencies for the 21st century. However, limited infrastructure and low technological literacy remain obstacles in a number of schools, including Moria High School in Sorong City. This activity aims to improve computer network technology literacy and students' speaking skills through a hands-on, practice-based training approach. The method used is qualitative with stages of observation, socialization, training, and evaluation. Computer network training includes an introduction to basic networking concepts, cabling practices, and network simulations using Cisco Packet Tracer. While speaking skills training is conducted through role-play techniques, repetition, and direct feedback. The results of the activity showed an increase in students' understanding of computer network technology, technical practical skills, and increased confidence and clarity in speaking. Evaluations showed that most participants were able to apply the material presented conceptually and practically. Thus, this activity has proven effective in improving students' computer network technology literacy and speaking skills as preparation for facing 21st-century learning and the world of work in the digital era.